Semantic search in Europeana: problem perceived but not the solution - Abadal, Ernest; Codina, Lluís (Anuario ThinkEPI, 2009)
The internet has facilitated the creation of large collections of documents by the aggregation of documents sent from different suppliers. Europeana is an example. In general, these documents have been identified using different thesauri and, at the same time, different languages. There are no systems that help the user to consult these documents using natural language, and also in their own language. Europeana has set up a prototype of a semantic search engine. In this text we analyze its structure and functioning. The conclusion, however, is that this is a very experimental version.